The Advantages from Cloud Computing Application Towards SMME (UMKM) - Az-zahra, Tazkia Shabrina (JOIN (Jurnal Online Informatika), 2019)
Small Micro Medium Enterprises (SMME) is one of the business enterprises that has a prime role in the development of economic growth in Indonesia. The SMME also not only reduces the number of jobless but also improve the community’s standard of living. Nonetheless, in this globalization era where the technology reaches its peak in every field, some SMME entrepreneurs have not taken advantage of IT-based business yet. On the other hand, the utilization of IT in the business field has many profitable benefits. This could make the SMME faced trouble and hard to survive in the tight competition with other bigger enterprises that had applied IT in the future. The main reason that SMME entrepreneur has not applied the IT system is that they lack fund. Moreover, cloud computing is a technology that can be used for every SMME entrepreneur without any costs. The advantages of this system utilization are to improve competitiveness, increase its flexibility, reduce costs, and to improve both agility and scalability. This research is based on a literature study that describes research’s aim that is to seek advantages from cloud computing implementation towards SMME in Indonesia so they can compete with international enterprises with a bigger scale. The researcher expects that SMME entrepreneurs in Indonesia can utilize Information technology particularly cloud computing, to support their business.